Solution Model for Enhancing the Experiences of Urban First Nations and Métis Patients Accessing and Navigating the Health System for Inflammatory Arthritis Care - Cheryl Barnabe; Jean Miller; Sylvia Teare; Casey Eaglespeaker; Brenda Roland; Nicole Eshkakogan; (Lynden) Lindsay Crowshoe; Elena Lopatina; Deborah Marshall (International Indigenous Policy Journal, 2019)
Health system innovations that better support Indigenous patients, particularly in urban settings, exist in primary health services, but this has not been translated and integrated into specialty care. We sought to identify the experiences of urban First Nations and Métis patients with inflammatory arthritis in accessing and navigating the health system. We used a qualitative research method called Patient and Community Engagement Research Program (PaCER) led by patients using an iterative three phase process: Set, Collect, and Reflect. Initial access and continuity of specialty care can be facilitated with collaboration between primary and specialty care in an urban Indigenous health service model, where health system change was built on culturally responsive models of care.